Transparency portals in development cooperation: More effectiveness and better communication? - Heiner Janus; Tim Röthel (German Institute of Development and Sustainability (IDOS), 2025)
Transparency portals in development cooperation serve two main functions: accountability to a specialist audience and communication with the wider public. In this policy brief, we conduct an international comparison to demonstrate how transparency portals could better fulfil these requirements. As part of a broader effectiveness agenda, donors are pursuing the goal of greater transparency. In line with this international agenda, transparency is intended to promote learning and improve predictability for partner countries, as well as combatting corruption and fulfilling accountability requirements. Taken together, these factors can contribute to greater development effectiveness. Donors also hope that their work will receive greater public support. By providing detailed information, experts will be better able to assess the quality of development projects. The aim is to initiate a process of learning and improvement, and to convince the general public that taxpayers' money is being used effectively. Citizens can use the portals to understand project content and develop their own views. However, current debates suggest a more complex dynamic. The "Bike Lanes in Peru" project caused a scandal in Germany. Against the backdrop of the closure of the US Agency for International Development (USAID), individual projects became politicised. Accordingly, transparency portals can also have unintended consequences. For example, information can be taken out of context, leading to misunderstandings and legitimate criticism of individual projects going unanswered. Donors can mitigate these negative effects by redesigning transparency portals. In times of declining approval ratings and cuts to development budgets, they should use the portals to communicate in a targeted manner and demonstrate a greater willingness to engage in honest debate. The following recommendations could help with this: Even greater transparency of impact data: Although progress is being made in transparent reporting on project content and financial data, detailed project data on impact measurement and results, as set out in logical frameworks (logframes), is lacking. Increasing transparency in this area could improve development effectiveness. Additional investment in communication: Information that is provided in accordance with internationally comparable standards must be translated for a lay audience. In many donor countries, a large proportion of the population has no fixed positive or negative attitude towards development cooperation. Targeted, group-oriented communication should appeal to these people more directly. Openness to criticism and discourse: Development policy actors often resist critical examination of their work in public debate. They tend to respond defensively to criticism, whether general or specific. However, informed discussions based on project data from the portals offer an opportunity to openly discuss ineffective projects and, if necessary, replace them with effective ones.
Keywords: 320; transparency; transparency portals; effectiveness; development cooperation; donor comparison; public opinion